2022
DOI: 10.1186/s12882-022-02796-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk of malignancy in kidney transplant recipients: a nationwide population-based cohort study

Abstract: Background Post-transplant malignancy is major morbidity complicated in kidney transplantation (KT). In Korea, a few studies have investigated the sex- and age-dependent risk for post-transplant malignancy among KT recipients on a large scale. Methods We utilized a national health insurance database in Korea to investigate the relative risk of post-transplant malignancy in 12,634 KT recipients between 2007 and 2017. The same number of patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The overall type and frequency of cancers diagnosed in our patient analysis are summarized in Table 2 . Previous studies have identified the association of certain cancers with transplant patients with chronic IMD use [ 28 , 29 , 30 , 31 , 32 ]. The risk of these factors has been reported as high for skin cancer (>10-fold increase), Kaposi sarcoma (>50-fold increase), non-Hodgkin’s lymphoma (>8-fold increase), and cancers of the anogenital tract (vaginal, cervical, vulval, anal, and penile cancer; >4-fold increase).…”
Section: Discussionmentioning
confidence: 99%
“…The overall type and frequency of cancers diagnosed in our patient analysis are summarized in Table 2 . Previous studies have identified the association of certain cancers with transplant patients with chronic IMD use [ 28 , 29 , 30 , 31 , 32 ]. The risk of these factors has been reported as high for skin cancer (>10-fold increase), Kaposi sarcoma (>50-fold increase), non-Hodgkin’s lymphoma (>8-fold increase), and cancers of the anogenital tract (vaginal, cervical, vulval, anal, and penile cancer; >4-fold increase).…”
Section: Discussionmentioning
confidence: 99%